Reliability of phase-specific outcome measurements in change-of-direction tests using a motorized resistance device - Westheim, Frederic; Gløersen, Øyvind; Harper, Damian; Laugsand, Håkon; Eriksrud, Ola (Frontiers in Sports and Active Living, 2023)
The aim of this study was to determine reliability of phase specific information during the initial acceleration, deceleration, and re-acceleration phases, of different change of direction (CoD) tests using a motorized resistance device (MRD). A total of 21 participants (16 males and 5 females; age 22.3 ± 3.9 years, body mass 75.2 ± 6.9 kg, height 177.9 ± 6.8 cm) completed the modified 505 (m505), 10-0-5 and 15-0-5 CoD tests on four different test sessions while exposed to an external load (3 kg) provided by the MRD. Outcome variables included overall and phase specific kinetic (force, power, and impulse) and kinematic (time, distance, velocity, and acceleration/deceleration) data during initial acceleration, deceleration, and re-acceleration. The deceleration and re-acceleration phases were further divided into early and late sub-phases using 50% of maximum velocity. Reliability was assessed using intraclass correlation coefficient (ICC), coefficient of variation (CV), typical error (TE) and minimal detectable change (MDC). Mostly good to excellent ICC values (> 0.75), and acceptable (< 10%) to good (< 5%) CV values were observed for all outcome measurements. Specifically, 80.1 % (822 out of 1026) of all variables showed good or better relative reliability (i.e., ICC ≥ 0.75), while 96.98 % (995 out of 1026) of all variables showed acceptable or better absolute reliability (i.e., CV <10 %). In conclusion, the present study shows that the MRD can obtain reliable phase specific outcome measurements across different CoD tests, providing coaches and researchers with new opportunities to advance our understanding of CoD ability and inform more advanced CoD training prescriptions.